A new method to support UMTS - Li Ma
This article proposes a new method to facilitate seamless vertical handover between wide area cellular data networks such as UMTS and WLANs using the stream control transmission protocol (SCTP). The multihoming capability and dynamic address configuration extension of SCTP are applied in UMTS/WLAN overlay architecture to decrease handover delay and improve throughput performance. Unlike techniques based on mobile IP or session initiation protocol, the SCTP-based vertical handover scheme does not require the addition of components such as home/foreign agents or a SIP server to existing networks. Therefore, the proposed scheme provides a network-independent solution preferred by service providers. Performance evaluations are presented to demonstrate the effectiveness of the proposed scheme.
Keywords: UMTS; WLAN; Dynamic address configuration extension; Multihoming capability; Stream control transmission protocol; Wide area cellular data networks